DEVELOPMENT TENDENCIES AND PROSPECTS OF PRIVATE SCHOOLS IN MODERN EDUCATION - Norova, Nargiza (MMIT Proceedings, 2023)
This article covers the privatization of knowledge institutions, their development trends and prospects as a result of the current development of Education. In addition, comparative considerations were made with private schools of foreign countries